Rheological Properties of Polyethylene and Polypropylene Modified Bitumen - Habib, Noor Zainab (2012)
This paper presents a part of research on the rheological properties of bitumen modified by thermoplastic namely linear low density polyethylene (LLDPE), high density polyethylene (HDPE) and polypropylene (PP) and its interaction with 80 pen base bitumen. As it is known that the modification of bitumen by the use of polymers enhances its performance characteristics but at the same time significantly alters its rheological properties. The rheological study of polymer modified bitumen (PMB) was made through penetration, ring & ball softening point and viscosity test. The results were then related to the changes in the rheological properties of polymer modified bitumen. It was observed that thermoplastic copolymer shows profound effect on penetration rather than softening point. The viscoelastic behavior of polymer modified bitumen depend on the concentration of polymer, mixing temperature, mixing technique, solvating power of base bitumen and molecular structure of polymer used. PP offer better blend in comparison to HDPE and LLDPE. The viscosity of base bitumen was also enhanced with the addition of polymer. The pseudoplastic behavior was more prominent for HDPE and LLDPE than PP. Best results were obtained when polymer concentration was kept below 3%